2016
DOI: 10.1097/pcc.0000000000000573
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Methylprednisolone on Plasma Concentrations of Neutrophil Gelatinase–Associated Lipocalin in Pediatric Heart Surgery*

Abstract: Preoperatively administered methylprednisolone profoundly decreases plasma neutrophil gelatinase-associated lipocalin levels. Neutrophil gelatinase-associated lipocalin seems to originate to a significant extent from activated neutrophils. Preoperative methylprednisolone is a confounding factor when interpreting plasma neutrophil gelatinase-associated lipocalin levels as a kidney injury marker in pediatric heart surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…This effect of on-pump surgery has also been demonstrated before [37]. Third, peri-operative methylprednisolone reduced plasma NGAL and LF similarly in pediatric cardiac surgery [38]. The latter is consistent with the fact that corticosteroids have been demonstrated to directly inhibit neutrophils [39].…”
Section: Discussionsupporting
confidence: 76%
“…This effect of on-pump surgery has also been demonstrated before [37]. Third, peri-operative methylprednisolone reduced plasma NGAL and LF similarly in pediatric cardiac surgery [38]. The latter is consistent with the fact that corticosteroids have been demonstrated to directly inhibit neutrophils [39].…”
Section: Discussionsupporting
confidence: 76%
“…Neutrophil gelatinase-associated lipocalin appears to come from active neutrophils to a large extent. When interpreting plasma neutrophil gelatinaseassociated lipocalin levels as a kidney damage marker in pediatric heart surgery, preoperative methylprednisolone can be a confusing factor [35]. After neonatal cardiopulmonary bypass surgery, prophylactic postoperative hydrocortisone lowers low cardiac output syndrome, improves fluid balance and urine output, and minimizes inflammation [39].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that high-dose methylprednisolone (MP) reduces activation of neutrophils, which are important first line actors in ischemia/reperfusion injury. 6 Furthermore, we have observed that MP conserves endothelial glycocalyx, a major determinant of capillary permeability and tissue edema. 7 The overall prognosis for congenital heart diseases has improved.…”
Section: Introductionmentioning
confidence: 90%